Design and Implementation of Information Retrieval using Ontology (Global Journal of Computer Science and Technology, 2014)
An approach is proposed that can be used to make these arch adaptive according to each user2019;s need using ontology .Our approach is distinct because it allows each user to perform more fine-grained search by capturing changes of each user2019;s preferences without any user effort. Such a method is not performed in typical search engines.
Keywords: ontology; fine-grained; user2019; s preferences; search engines